1986
DOI: 10.1128/jvi.57.3.729-737.1986
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency RNA recombination of murine coronaviruses

Abstract: The RNA genome of coronaviruses consists of a single species of nonsegmented RNA. In this communication, we demonstrate that the RNA genomes of different strains of murine coronaviruses recombine during mixed infection at a very high frequency. Susceptible cells were coinfected with a temperature-sensitive mutant of one

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
251
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(259 citation statements)
references
References 34 publications
7
251
0
Order By: Relevance
“…Another important mechanism for CoV genetic evolution is the high frequency of homologous RNA recombination (Lai et al, 1985;Makino et al, 1986). This process is believed to be mediated by a ''copychoice'' mechanism (Cooper et al, 1974;Kirkegaard and Baltimore, 1986;Makino et al, 1986).…”
Section: Epiloguementioning
confidence: 99%
See 1 more Smart Citation
“…Another important mechanism for CoV genetic evolution is the high frequency of homologous RNA recombination (Lai et al, 1985;Makino et al, 1986). This process is believed to be mediated by a ''copychoice'' mechanism (Cooper et al, 1974;Kirkegaard and Baltimore, 1986;Makino et al, 1986).…”
Section: Epiloguementioning
confidence: 99%
“…Another important mechanism for CoV genetic evolution is the high frequency of homologous RNA recombination (Lai et al, 1985;Makino et al, 1986). This process is believed to be mediated by a ''copychoice'' mechanism (Cooper et al, 1974;Kirkegaard and Baltimore, 1986;Makino et al, 1986). Recombination of CoV genomes has been observed during growth in tissue cultures (Lai et al, 1985;Makino et al, 1986;Sanchez et al, 1999;Kuo et al, 2000), in experimentally infected animals (Keck et al, 1988), and in embryonated eggs (Kottier et al, 1995).…”
Section: Epiloguementioning
confidence: 99%
“…Nevertheless, as the restraint of error threshold of lethal mutations, the coronavirus is speculated to have a relatively low mutation rate due to its large genome size (Eigen, 1987;Maynard Smith and Szathmá ry, 1995). To increase viral adaptability and fitness, coronavirus has evolved a unique discontinuous transcription system and 'copy-choice' genomic synthesis to achieve high efficiency of RNA recombination (Cavanagh, 2007;Lai et al, 1985;Liao and Lai, 1992;Makino et al, 1986). However, only sporadic recombinant variants have been detected in nature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to point mutation, RNA recombination is also involved in the generation of new antigenic variants. RNA recombination in a coronavirus was first demonstrated experimentally in mouse hepatitis virus (MHV) (Lai et al, 1985;Makino et al, 1986), and a high frequency of recombination was found both in vitro and in vivo after MHV infection (Keck et al, 1988;Makino et al, 1986). Recombination sites were detected throughout nearly the entire genome, and many recombinants with multiple crossover sites were found (Liao and Lai, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation